2022
DOI: 10.3390/nu14204348
|View full text |Cite
|
Sign up to set email alerts
|

Lotus (Nelumbo nucifera Gaertn.) Leaf-Fermentation Supernatant Inhibits Adipogenesis in 3T3-L1 Preadipocytes and Suppresses Obesity in High-Fat Diet-Induced Obese Rats

Abstract: The lotus (Nelumbo nucifera Gaertn.) leaf is a typical homologous ingredient of medicine and food with lipid-lowering and weight-loss effects. In the present study, lotus leaves were fermented by two probiotics, Enterococcus faecium WEFA23 and Enterococcus hirae WEHI01, and the anti-adipogenic effect of Enterococcus fermented lotus leaf supernatant (FLLS) was evaluated in 3T3-L1 preadipocytes with the aim of exploring whether its anti-obesity ability will be enhanced after fermentation with Enterococcus and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…nucifera seeds was mainly used for neuroprotection. , However, it is rich in alkaloids that are highly similar to the leaf of N. nucifera, suggesting that embryo of N. nucifera seeds may also have antiobesity potential.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…nucifera seeds was mainly used for neuroprotection. , However, it is rich in alkaloids that are highly similar to the leaf of N. nucifera, suggesting that embryo of N. nucifera seeds may also have antiobesity potential.…”
Section: Resultsmentioning
confidence: 99%
“…The embryo of N. nucifera seeds was mainly used for neuroprotection. 30 , 31 However, it is rich in alkaloids that are highly similar to the leaf of N. nucifera , 13 15 suggesting that embryo of N. nucifera seeds may also have antiobesity potential. Based on this, we studied the alkaloids of embryo of N. nucifera seeds and explored their biological activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, studies have shown that the biological activity of many herbs, including MFH, is achieved through biotransformation by intestinal microbiota (Hussain et al., 2016). Evidence has been accumulating in recent years that probiotic‐fermented MFH has beneficial effects on human health, including the prevention and control of disease (He et al., 2022; Shen et al., 2022). Probiotic‐driven fermentation enhances/alters the effectiveness of MFH by transforming and releasing its active ingredients, thereby promoting human health and improving its sensory properties, as well as extending its shelf life (Leonard et al., 2021; Torres et al., 2020).…”
Section: Introductionmentioning
confidence: 99%